(untitled) (Bangladesh Journal of Zoology, 2015)
Bacterial isolates, Bacillus firmus (LS-31) were collected from eutrophic Gulshan lake, Dhaka sediments and introduced to stimulate inorganic nutrient regeneration in the laboratory. The bacteria stimulated net regeneration of dissolved inorganic nitrogen and inorganic phosphorus in the water by about two folds at both the incubation temperatures (26°C and 30°C). These results suggest that the application of B. firmus would be promising for the stimulation of inorganic nutrient regeneration at the eutrophic environment. Bangladesh J. Zool. 41(1): 73-78, 2013